2004
DOI: 10.1152/japplphysiol.00148.2004
|View full text |Cite
|
Sign up to set email alerts
|

New replicable anxiety-related measures of wall vs. center behavior of mice in the open field

Abstract: Anxiety is a widely studied psychiatric disorder and is thought to be a complex and multidimensional phenomenon. Sensitive behavioral discrimination of animal models of anxiety is crucial for the elucidation of the behavioral components of anxiety and the physiological processes that mediate them. Commonly used behavior paradigms of anxiety usually include only a few automatically collected measures; these do not exhaust the behavioral richness exhibited by animals, thus perhaps missing important differences b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
101
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 129 publications
(108 citation statements)
references
References 36 publications
4
101
0
3
Order By: Relevance
“…Our current study of free exploration is a single laboratory experiment, so we turn to explain this point by using interstrain differences in the number of incursions per session as analyzed in forced exploration (24), wherein experiments were performed simultaneously in three laboratories according to a standardized experimental and housing protocol (Materials and Methods and SI Materials and Methods). The demand for replicability of the strain difference in the number of incursions per session across laboratories (captured by the mixed-model analysis in ref.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our current study of free exploration is a single laboratory experiment, so we turn to explain this point by using interstrain differences in the number of incursions per session as analyzed in forced exploration (24), wherein experiments were performed simultaneously in three laboratories according to a standardized experimental and housing protocol (Materials and Methods and SI Materials and Methods). The demand for replicability of the strain difference in the number of incursions per session across laboratories (captured by the mixed-model analysis in ref.…”
Section: Discussionmentioning
confidence: 99%
“…The arena wall, like the home base, acts as a reference and attractor during forays into the center of the arena: in several mouse strains, motion away from the wall is slower than motion toward it (24). Whereas sighted mice move faster toward the wall than away from it, blind mice use similar speeds in both directions (25).…”
Section: Evidence For Sequences Of Repeated Motion Away From and Back Tomentioning
confidence: 99%
See 1 more Smart Citation
“…Thus the key to applying a data mining approach in behavioral analysis is designing a useful 'chip', that is, constructing a proper categorization of the data into multiple types of behavior that can be mined. To this end the units employed by PA consist of a large number (B100 000) of complex movement patterns, algorithmically defined as simultaneous combinations of several ethologically relevant 'attributes' such as the distance from the arena wall (Broadhurst, 1975;Leppanen et al, 2005;Lipkind et al, 2004), the speed and acceleration of movement (Kafkafi et al, 2003b), direction of movement (Horev et al, 2007), and turning . For example, by using the three attributes of acceleration, distance from the wall and turning, a specific movement pattern in PA may be defined as the combination 'heavily braking while moving near the wall but turning slightly away from it'.…”
Section: Introductionmentioning
confidence: 99%
“…It was situated in a room containing distal visual cues with light level set between 80 and 100 Lux and was placed under a camera connected to a video-track system that allows the discrimination of navigatory -speed > 11.8cm/sec-and exploratory movements -speed < 6.8cm/sec- [17]. It has been shown that rodents spontaneously avoid the center of a large open area which is more brightly illuminated than the periphery [21]. We therefore used the number of visits and time spent in the center as an index of anxiety during free exploratory activity.…”
Section: Introductionmentioning
confidence: 99%